2011
DOI: 10.1378/chest.10-1795
|View full text |Cite
|
Sign up to set email alerts
|

Staff Acceptance of Tele-ICU Coverage

Abstract: A lthough intensivist care is associated with lower ICU and hospital mortality and with reduced length of stay, 1 only one-third of critically ill patients receive intensivist care, and the shortfall is projected to worsen. 2 As a result, hospitals increasingly rely on tele-ICU coverage. 3 For the purposes of this article, we defi ne tele-ICU coverage as the application of telemedicine 4 to in-hospital critical care units, thereby encompassing an array of technologies of varying complexity 5,6 that allow physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
51
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(58 citation statements)
references
References 22 publications
4
51
0
3
Order By: Relevance
“…For example, McCambridge et al [17] characterized the tele-ICU as one component of a coordinated health care information technology bundle. The governance structure of ICU care within the University of Massachusetts-Memorial health care system was restructured and centralized before a tele-ICU implementation [3]. In our work, we limited changes within the ICU to 2-way audiovisual communication and tele-ICU staffing.…”
Section: E13mentioning
confidence: 99%
See 2 more Smart Citations
“…For example, McCambridge et al [17] characterized the tele-ICU as one component of a coordinated health care information technology bundle. The governance structure of ICU care within the University of Massachusetts-Memorial health care system was restructured and centralized before a tele-ICU implementation [3]. In our work, we limited changes within the ICU to 2-way audiovisual communication and tele-ICU staffing.…”
Section: E13mentioning
confidence: 99%
“…Telemedicine is a complex sociotechnical intervention, and the context regarding how it is implemented and supported and the type of organizations in which it is used may influence its impact Young et al [3]. We chose to use a consultative care model so that it could be uniformly applied to all patients in the test ICU.…”
Section: E13mentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, providers such as intensivists have been decreasing in numbers, causing a shortage of care practitioners. 10 According to a 2006 Health Resources and Services Administration study, the United States will need as many as 4,300 critical care physicians by 2020, and a 1,500 intensivist shortfall is predicted. 11,12 Physicians trained as intensivists who provide care via tele-ICU have been able to help fill this gap in order to deliver more effective healthcare.…”
Section: Introductionmentioning
confidence: 99%
“…13 It has been suggested that tele-ICU implementation and utilization have the potential to be as effective as having dedicated intensivists in the ICU 24 h/day, relieving taxed staff, and providing quality care to the ever-increasing ICU patient population. 10 The purpose of this study was to determine the potential impact and direction of the implementation of the tele-ICU in hospitals to assess current benefits and barriers of adoption of this technology.…”
Section: Introductionmentioning
confidence: 99%